Sastra drama : perjalanan, perkembangan, dan pengkajiannya - Rahayu, Lina Meilinawati, 1970-; Hendayana, Yayat, 1943- (Bandung : Sastra Unpad Press, 2010)
History of Indonesian drama.
Includes bibliographical references (p. [155]-158).
Keywords: Indonesian drama -- History and criticism